Betacoronavirus Assembly: Clues and Perspectives for Elucidating SARS-CoV-2 Particle Formation and Egress - David Bracquemond (American Society for Microbiology, 2021)
In 2019, a new pandemic virus belonging to the betacoronavirus family emerged, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This new coronavirus appeared in Wuhan, China, and is responsible for severe respiratory pneumonia in humans, namely, coronavirus disease 2019 (COVID-19).